Analysis of grain orientation and defects in Sb2Se3 solar cells fabricated by close-spaced sublimation. (1st September 2021) - Krautmann, R.; Spalatu, N.; Gunder, R.; Abou-Ras, D.; Unold, T.; Schorr, S.; Krunks, M.; Oja Acik, I.
Highlights: Seed layer deployment clearly improved performance of TiO2 /Sb2 Se3 solar cells. Pole figures revealed seed layer enhanced texture of Sb2 Se3 along [001] direction. Temperature-dependent admittance spectroscopy detected deep defect at 0.39 eV. Capacitance-voltage profiles show the defect density could be as high as 10 17 cm −3 . Abstract: The performance of a superstrate TiO2 /Sb2 Se3 solar cell, fabricated by close-spaced sublimation technique (CSS), was improved after the deployment of a seed layer. The seed layer caused columnar Sb2 Se3 film growth with texture coefficient analysis (TC) showing increased presence of crystal planes, which are inclined towards the [001] crystal direction. Given the highly anisotropic properties of Sb2 Se3, preferential growth of (Sb4 Se6 )n ribbons along the [001] direction is best suited for effective charge collection. Hence, grain orientation of Sb2 Se3 films was studied more closely via measurement of pole figures by XRD and orientation distribution maps by electron backscatter diffraction (EBSD). Although the measurements did not reveal strong preferred orientation, it was observed that the columnar Sb2 Se3 growth enhanced texture along the [001] direction. Temperature-dependent admittance spectroscopy (TAS) and capacitance–voltage (CV) profiling were performed on the seed-assisted TiO2 /Sb2 Se3 solar cell to evaluate carrier density and deep defects in the Sb2 Se3 absorber. TAS study revealed a deep defect with activation energy of 0.39 eV. CV profiles indicated that the density of defects could be as high as 10 17 cm −3, which needs to be addressed by post-deposition treatments.